Positive and Negative Face Analysis in Big Hero 6 Movie: A Pragmatics Study - Jengsen Siagian; Ervina CM Simatupang (Ethical Lingua: Journal of Language Teaching and Literature, 2022)
The research purposes to describe the functions and types of positive and negative faces found in Big Hero 6 movie. In this study, Big Hero 6 is a movie which has positive and negative face approaches; thus, it has been analysed by the appropriate instruments and methods. The research approach used is qualitative with descriptive methods from direct observations of each scene in the Big Hero 6 movie. The data was taken from the Big Hero 6 movie. The theories used to analyse the data were from Brown and Levinson (1978). The research resulted that the positive and negative face features in this movie are closely related to their value in anti-violence. The negative face in Big Hero 6, on the one hand, is closely related to how then one of the characters in this movie tends to want to solve problems quickly through violence and individually. While the positive side of this movie is shown by how the other characters in this movie also try to prevent acts of violence by solving problems as much as possible. The research findings show that there are 26 conversational data showing positive and negative faces, in this study the researchers only showed 7 data of evidence showing positive face 4 and negative face 3.